2018
DOI: 10.1111/sji.12653
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oxidative stress and antioxidant status: Correlation with the severity of sepsis

Abstract: Sepsis is a condition caused by infection followed by unregulated inflammatory response which may lead to the organ dysfunction. During such condition, over-production of oxidants is one of the factors which contribute cellular toxicity and ultimately organ failure and mortality. Antioxidants having free radicals scavenging activity exert protective role in various diseases. This study has been designed to evaluate the levels of oxidative and antioxidative activity in sepsis patients and their correlation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
65
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 53 publications
(93 reference statements)
8
65
0
7
Order By: Relevance
“…[20] Similarly, Kumar et al reported augmented levels of oxidants in patients with sepsis as demonstrated by DMPO nitrone adduct formation and plasma myeloperoxidase (MPO) level activity. [21] In this study the SOFA and APACHE II scores correlated linearly with the MPO levels and inversely with the levels of antioxidants. This study supports the concept that the imbalance between oxidant and antioxidants plays key role in the pathophysiology of organ failure in sepsis.…”
supporting
confidence: 50%
“…[20] Similarly, Kumar et al reported augmented levels of oxidants in patients with sepsis as demonstrated by DMPO nitrone adduct formation and plasma myeloperoxidase (MPO) level activity. [21] In this study the SOFA and APACHE II scores correlated linearly with the MPO levels and inversely with the levels of antioxidants. This study supports the concept that the imbalance between oxidant and antioxidants plays key role in the pathophysiology of organ failure in sepsis.…”
supporting
confidence: 50%
“…There is an alteration to the pro-oxidant-antioxidant balance. Also, there is an increase in the concentration of inflammatory cytokines (TNF-α and IL-8) and a decrease in the plasma activity of superoxide dismutase (SOD) and catalase (CAT) [16]. TNF-α and IL-8 exert cardiac depression by reducing myocardial shortening [17], further jeopardizing the patient's hemodynamics.…”
Section: Sepsis As a Healthcare Problemmentioning
confidence: 99%
“…Oxidative stress is the serious cause of organ disability in critically ill patients (Ghashut et al, 2017). Reducing the antioxidant capacity (Rogobete et al, 2017) in these patients due to inefficient oxidative phosphorylation (Lorente et al, 2018) leads to an increase in free radicals (Oliveira, Pontes-de-Carvalho, Couto, & Noronha-Dutra, 2017), which is actually a possible mechanism for damage caused by the sepsis (Kumar et al, 2018). Some natural compounds and herbal derivatives have anti-inflammatory and antioxidant effects that can improve sepsis symptoms, such as zinc (Ganatra et al, 2017), magnesium (Esen et al, 2004), Q10 (Abitagaoglu et al, 2015), and curcumin (Chen, Lu, et al, 2018).…”
mentioning
confidence: 99%